AI Determinants of Organizational Performance of English Training Institutions in China - Li, Na (Transformations In Business & Economics, 2025)
Using a multivariate multiple linear regression analysis, this study examines the effect of AI adoption measures (organizational AI investment, intelligent tutoring systems, adaptive learning platforms, culturally sensitive AI tools, & faculty training in AI) on the different metrics of organizational performance (student enrollment growth, personalized learning experience, enhanced student engagement, improved teaching efficiency, & organizational revenue growth) of China’s English training institutes. The study findings reveal that AI incorporation significantly improves the organizational performance of English training institutions in China, illuminating the strategic role of investing in AI-driven technologies such as adaptive learning platforms, organizational AI investment, culturally sensitive AI tools, intelligent tutoring systems, and faculty trainings in AI. In specific, intelligence tutoring systems and adaptive learning platforms exhibit the most substantial effect on organizational performance, validating their versatility and effectiveness in supplementing both financial/economic and educational performance. Similarly, culturally sensitive AI tools result in improved student engagement and inclusivity, emphasizing the importance of cultural considerations in AI integrations. Besides this, organizational AI investment and faculty training in AI also play a pivotal role, particularly in fostering personalized learning experience and organizational revenue growth. Thus, the research inferences proposed in this study put forward useful theoretical and practical implications for educators, policymakers, and business managers. AI adoption acts as a strategic tool to address long-run issues associated with enrollment stagnation, cost inefficiencies, business operations, and financial performance. Therefore, institutional managers must perceive AI not merely as a technological upgrade but as an integral element of organizational strategy that supports operational efficiency, financial sustainability, and long-term growth.